The evolutionary dynamics of α-satellite - Rudd, M. Katharine; Wray, Gregory A.; Willard, Huntington F.

(untitled) (Genome Research, 2006)
α-Satellite is a family of tandemly repeated sequences found at all normal human centromeres. In addition to its significance for understanding centromere function, α-satellite is also a model for concerted evolution, as α-satellite repeats are more similar within a species than between species. There are two types of α-satellite in the human genome; while both are made up of ∼171-bp monomers, they can be distinguished by whether monomers are arranged in extremely homogeneous higher-order, multimeric repeat units or exist as more divergent monomeric α-satellite that lacks any multimeric periodicity. In this study, as a model to examine the genomic and evolutionary relationships between these two types, we have focused on the chromosome 17 centromeric region that has reached both higher-order and monomeric α-satellite in the human genome assembly. Monomeric and higher-order α-satellites on chromosome 17 are phylogenetically distinct, consistent with a model in which higher-order evolved independently of monomeric α-satellite. Comparative analysis between human chromosome 17 and the orthologous chimpanzee chromosome indicates that monomeric α-satellite is evolving at approximately the same rate as the adjacent non-α-satellite DNA. However, higher-order α-satellite is less conserved, suggesting different evolutionary rates for the two types of α-satellite.